Renewing an undergraduate science curriculum for the 21st century - McAteer, Louise; Roche, Joseph; Kelly, Áine M. (Frontiers in Education, 2023)
The rapid pace of technological advancement, globalisation, and complex socio-economic challenges facing 21st-century society necessitates a rethinking of undergraduate science education. Undergraduate science curriculum reform is essential to prepare students for the demands of the modern workforce in an ever-changing world. Accordingly, in Trinity College Dublin (the University of Dublin), the oldest science degree course in Ireland was intensively reviewed and redeveloped between 2014 and 2021. This study aims to collate and disseminate the knowledge acquired by university staff through the experience of undertaking a major science curriculum redevelopment. Nine senior staff members closely involved with the redevelopment were interviewed about why the curriculum reform was necessary, what it had achieved, and how the process could have been improved. The reasons behind the curriculum changes are described and placed in the context of contemporary pedagogical research. Reflections from the academic and administrative staff involved in the redevelopment process are presented, emphasising the challenges and opportunities that emerged from that process. Recommendations for other universities undertaking similar reforms are included. Aligning undergraduate science curriculum reform with the needs of 21st-century society is vital for ensuring that science graduates are well-prepared to make positive contributions to a sustainable future.